Reliability-oriented performance evaluation of PV inverters using wide bandgap semiconductors - Sainadh Singh Kshatri; Javed Dhillon; Sachin Mishra; Naveen Kumar Sharma; Vinay Kumar Jadoun (PLoS ONE, 2026)
The recent development of power electronic devices that utilizes the advantages of wideband gap semiconductor components for electrical conversion is expected to create a new class of reliable and efficient inverters. However, the photovoltaic inverter is considered a critical component in grid-connected PV systems with respect to reliability performance. Therefore, this paper proposes a wide-bandgap semiconductor (WBS) based photovoltaic inverter, specifically utilizing silicon carbide (SiC) MOSFETs and gallium nitride (GaN) HEMTs, to enhance reliability and performance. In this paper, reliability-oriented performance is evaluated on a grid connected 3 kW photovoltaic (PV) inverter system under real-time Mission Profile (MP) in India. Environmental factors are assessed based on a one-minute resolution yearly MP, in which solar irradiance (SI) and ambient temperature (AT) are considered. To model the lifetime with a two-Parameter Weibull distribution, the Monte Carlo simulation (MCS) is utilized to produce 10,000 samples with 5% parameter variation. The B 10 lifetime a reliability measure indicating the time by which 10% of population are expected to fail, is calculated for the Narsapur, Indian location and analyzed with regard to performance metrics, such as PV power, switch losses, inverter efficiency, and output power. In addition, this study compares the performance of conventional IGBT, super junction MOSFET (SJ-M), silicon carbide (SiC) MOSFET (SiC-M), and gallium nitride (GaN) HEMT (GaN-H) based inverters. Results show that WBG semiconductors can increase reliability and efficiency by eliminating 40% of losses compared to the conventional IGBTs.